Genome-wide identification and characterization of the ALBA gene family in rapeseed (Brassica napus L.) and its role in development and abiotic stress responses - Xu, Penghui; Chen, Zhenzhong (Frontiers in Plant Science, 2026)
ALBA proteins (Acetylation lowers binding affinity) are an ancient group of DNA- and RNA-binding proteins found in archaea, bacteria, and eukaryotes. These small, basic, dimeric proteins perform diverse functions, including roles in RNA metabolism, transcriptional and translational regulation, and stress responses. In this study, 29 ALBA-coding genes were identified for the first time in the rapeseed genome, showing an uneven chromosomal distribution. Evolutionary analyses classified these genes into two subfamilies, RPP-20 and RPP-25, with the latter characterized by longer sequences due to the presence of RGG-box domains. Exon–intron structures and conserved motifs displayed distinct patterns between the two subfamilies. Segmental/whole genome duplication (WGD) were the primary forces driving the expansion of this gene family, while paralogous gene pairs were found to be under purifying selection, indicating conservation of their functional roles throughout evolution. Strong collinearity was also observed with Arabidopsis, B. rapa, and B. oleracea. The presence of cis-acting regulatory elements (CAREs) related to stress and hormone responses, growth and development, and circadian regulation, along with post-transcriptional regulation by miRNAs, suggests that BnALBA genes are subject to complex regulatory control and play essential roles in rapeseed growth and environmental adaptation. Transcriptome data from multiple tissues and developmental stages revealed distinct expression profiles, with some genes showing low expression, others being specifically activated in certain tissues or stages, and some displaying overlapping expression patterns. qRT-PCR analysis further confirmed that BnALBA genes respond significantly to abiotic stresses, with BnALBA9 and BnALBA22 being strongly induced under salt stress, while BnALBA5, BnALBA9, and BnALBA27 showed substantial and consistent upregulation under drought stress. Together, these findings provide the first comprehensive identification and characterization of the ALBA gene family in rapeseed, underscoring their critical roles in regulating growth, development, and stress responses. This work establishes a foundation for future research aimed at improving rapeseed yield and resilience under adverse environmental conditions.